Analisis Peramalan Penjualan pada PT. Multi Megah Mandiri untuk Tahun 2009 - Yuliany Sylvia Agustina; Haryadi Sarjono (Fakultas Bisnis UKDW, 2010)
PT. Mthi Megah Merdrri is a compary that runs a mantfacturebusiness. The entire manufacfuring processes oe done in the compoty. The writer also mafue.s which netlrod is the best mtong thefwe methods based an the result of the smallest etrors of the l,E and the MAD. The'metlnds usedhere are Moving Average, Double Mwing Average, Weighted Moving overage, Expanenfi.al smoothing